The effects of whole-body compression garments on prolonged high-intensity intermittent exercise - Sear, J. A.; Hoare, T. K.; Scanlan, A. T.; Abt, G. A.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2010)
The current study investigated the effects of wearing whole-body compression garments (WBCGs) on prolonged high-intensity intermittent exercise (PHIIE) performance. Eight male team-sport athletes ([X¯ ± SD] 20.6 ± 1.2 years; 72.9 ± 5.9 kg; 57.5 ± 3.7 ml/kg·min) completed a prescribed 45-minute PHIIE protocol on a nonmotorized treadmill in randomly assigned WBCG and control (typical soccer apparel) conditions. Subjects were given verbal and visual cues for movement categories, and they followed set target speeds, except when instructed of a variable run or sprint where the aim was to run as fast as possible. Total distance, velocity-specific distance, and high-intensity self-paced running speeds were taken as performance indicators. Heart rate, VO2, tissue oxygenation index (TOI), and tissue hemoglobin index (nTHi) were continuously monitored across the protocol. Blood-lactate concentration ([BLa-]) was measured every 15 minutes. Magnitude-based inferences suggested that wearing WBCGs provided moderate strength likely improvements in total distance covered (5.42 ± 0.63 vs. 5.88 ± 0.64 km; 88:10:2%; and ny2 = 0.6) and low-intensity activity distance (4.21 ± 0.51 vs. 4.56 ± 0.57 km; 83:14:3%; and ?2 = 0.6) compared with the control. A similar likely increase was also observed in the average TOI of the WBCG condition (53.5 ± 8.3% vs. 55.8 ± 7.2%; 87:11:2%; and ?2 = 0.6). The current data demonstrated that wearing WBCGs likely increased physical performance, possibly because of improvements in muscle oxygenation and associated metabolic benefits. Therefore, wearing WBCGs during PHIIE may benefit the physical performance of team-sport athletes by likely metabolic changes within the muscle between high-intensity efforts.